2020
DOI: 10.1080/14763141.2020.1712469
|View full text |Cite
|
Sign up to set email alerts
|

The effect of match fatigue in elite badminton players using plantar pressure measurements and the implications to injury mechanisms

Abstract: The purpose of this study was to investigate the differences in plantar pressure under the lead and trail foot between two lunge tasks to the net in the dominant (LD) and nondominant (LND) directions, and to explore how fatigue affects the plantar pressure patterns whilst performing movements before and after a competitive match. Peak and mean pressure were measured with the Biofoot-IBV in-shoe system from five repetitions of each task, with sensors positioned under the calcaneus, midfoot and phalanges on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 67 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Plantar pressure was investigated in four included articles ( Hong et al, 2014 ; Hu et al, 2015 ; Mei et al, 2017 ; Valldecabres, Richards & De Benito, 2020 ). Typically, the footprint was divided into lateral and medial rearfoot, lateral and medial midfoot, metatarsal, hallux, and other toes regions to study plantar loading between interventions.…”
Section: Review Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Plantar pressure was investigated in four included articles ( Hong et al, 2014 ; Hu et al, 2015 ; Mei et al, 2017 ; Valldecabres, Richards & De Benito, 2020 ). Typically, the footprint was divided into lateral and medial rearfoot, lateral and medial midfoot, metatarsal, hallux, and other toes regions to study plantar loading between interventions.…”
Section: Review Contextmentioning
confidence: 99%
“…Peak pressure, maximum force, pressure–time-integral, and contact area were common parameters to evaluate plantar pressure profiles in the included articles. These outcome parameters describe the quality and efficiency of footwork in addition to the loading strategy and fatigue conditions ( Valldecabres, Richards & De Benito, 2020 ). For example, the speed on reaching the shuttlecock, impact attenuation capability, and movement stabilization to avoid injury ( Hu et al, 2015 ).…”
Section: Review Contextmentioning
confidence: 99%
“…Through these mechanical analyses, investigations have revealed the impact and potential damage to the lower limbs of players during lunging movements. For example, Valldecabres et al [3] found that plantar pressure transferred to the medial side of the forelimb and midfoot when players lunged with non-dominant limbs when fatigued in a study of 13 class A badminton league players. Lam et al [4] found that repetitive movements (RM) when lunging produced a smaller load rate on the knee than a single movement (SM) lunge.…”
Section: Introductionmentioning
confidence: 99%
“…Andrew et al [ 10 ] studied that neuropathic diabetic patients with foot ulceration have abnormally high pressure under the feet during walking. The significant applications of plantar pressure measurement include analyzing different body postures [ 11 ], sports biomechanics [ 12 ], biomedical especially diagnosis of foot-related diseases [ 13 ], designing footwear in the shoe industry [ 14 ], athlete performances [ 15 ], several sports activities [ 16 ], observing dynamics of obese people, monitoring posture allocation and human’s daily life activities such as standing, walking, jogging and running [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%